Bicycle-spoke injuries of the foot and ankle: A prospective study - Gupta, HK; Shrestha, R (Journal of College of Medical Sciences-Nepal, 2014)
Objective Bicycle spoke wheel injuries can be as simple as minor abrasions and lacerations even to amputation of toes and heel injuries. The purpose of this study was to assess the severity of soft tissue damage and skeletal injuries in such injuries. Methods This prospective observational study included all the cases with spoke wheel injuries presenting between October 2012 to September 2013 in the College of Medical Sciences and Teaching Hospital, Bharatpur. Demographic information was collected from each patient including age, sex, injured side, position at the time of injury, and characteristic of injury. The soft tissue injury was classified according to Oestern and Tscherne classification and managed accordingly. Results A total of 50 cases were included in the study with 29 males ( 58%) and 21 females (42% ). Their age ranged from 6 yrs to 12 yrs (mean 9 yrs.). The mean interval from injury to presentation in hospital was 5 hrs (range 1-22 hrs). Majority had injury to right ankle and foot. Fore foot and mid foot injuries were more common when the feet got entrapped in front wheel. 36 cases had sustained injury while riding as pillion on the back seat and their injury was on posterior ankle (n=20) and posterolateral aspect of ankle and foot (n=16). Majority of cases were of grade 0 and 1 injury. Two patients had grade 3 injury, one with great toe amputation another with partial heel avulsion and exposed tendoachilles. All cases were managed with wound care, tetanus prophylaxis and splintage of the foot. Conclusion In our study we found that these spoke wheel related injuries were more common in children and are important cause of temporary loss of daily activities. Although all injuries healed properly, risk of severe injuries like amputations and heel pad loss and tendoachilles transaction and fractures of foot and ankle still prevails where bicycle is a common mode of transportation. Journal of College of Medical Sciences-Nepal, 2013, Vol-9, No-4, 36-39 DOI: http://dx.doi.org/10.3126/jcmsn.v9i4.10236